Perancangan User Interface dan User Experience Adaptive Mobile Learning Untuk Siswa Sekolah Menengah - Rakhma Shafrida Kurnia; Bayu Pujiarti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to design and analyze the user interface (UI) and user experience (UX) of mobile-based learning (m-learning) applications that implement Adaptive learning. The design method is Design Science Research Methodology (DSRM). A poorly designed user interface can lead to a negative user experience, not using the software properly and continuously. On the other hand, UI can make using software easy and enjoyable, so a well-designed UI of learning apps can produce a pleasant learning experience for students. Adaptive learning is expected to be a method used as a means to balance learning needs to make it more efficient and effective to use. In the Evaluation stage, the User Experience Questionnaire (UEQ) is used which is grouped into six parameters, namely: attractiveness, clarity, Efficiency, accuracy, Stimulation , and Novelty. Based on the results of the Evaluation using UEQ, the mean values ​​obtained for all parameters are in the range of positive values ​​of more than 0.8. The user experience aspect in the form of Attractiveness is in the good category, the clarity aspect is in the above average category, the Efficiency aspect is in the good category, the accuracy is in the above average category, the Stimulation aspect is in the good category, and the Novelty aspect is in the above average category. The implementation of Adaptive learning on the UI and UX of the application has been well received by potential users based on the results of the Demonstration and Evaluation stages.